RANCANG BANGUN PROTOTIPE MONITORING SUHU RUANG SERVER MENGGUNAKAN SISTEM ARDUINO UNO ATMEGA328 DENGAN SENSOR LM35 PADA PT. X DI BATAM - Hadiyanto, Gunawan T; JN, Jumadril (Universitas Gajah Putih, 2020)
In the world of information technology today, very important server roles and networks. The impact of temperature out of tolerance, resulting in damage to the hardware in the server room from the room temperature is too hot or cold can be related by cooling the room off without being noticed by admin or manager server. However the monitoring and measurement of the temperature of server rooms cannot be directly and accurately in all conditions caused some inhibiting factor in obtaining the temperature information. With these problems, then built a prototype system using the temperature information Arduino Uno ATMega328 microcontroller which has the capability or feature information displays temperature data on LCD and alarm warning like buzzer.